KEPUASAN KERJA KARYAWAN DI DAERAH ISTIMEWA YOGYAKARTA: FAKTOR-FAKTOR YANG MEMPENGARUHINYA - Anton Prasetyo (Fokus Bisnis : Media Pengkajian Manajemen dan Akuntansi, 2018)
ABSTRACTThis study aims to determine whether the motivation, ethical leadership and rewards influence both jointly or individually / individually on employee job satisfaction in the Special Region of Yogyakarta. The number of samples in this study were 131 employees in the Special Region of Yogyakarta, using a modified Likert model questionnaire. Variable in this research there are 4, that is job satisfaction, motivation, ethical leadership and reward. The hypothesis in this research was tested by using multiple linear regression and using SPSS software. The results of this study indicate that motivation, ethical leadership and reward have the successive significance of 0.002; 0.028; 0.003 (<0.05) and the coefficient shows a positive sign or supported. While the F test shows the significance of 0.00 (<0.05), so it can be concluded that simultaneous of motivation, ethical leadership and reward are supported.Keywords: motivation; ethical leadership; reward; job satisfaction.